Limbah bahan berbahaya dan beracun (B3) - D Karyadi (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1995)
The waste of B3 is every waste contain of a dangerous anfd of or toxic goods. B3 waste can be produced from specific source, nort specific source and dispodal chemicals. B3 waste has one or more characteristic as follow : corrosive reactive, easy to burm, easy to explode, toxic and infection. Every body or enterprice is not permitted to import B3 waste from abroard to Indonesia or vice versa without permission from the Government of Indonesia Republic. INTISARI Limbah B3 adalah setiap limbah yang mengandung bahan berbahaya dan atau beracun. Limbah B3 dapat dapat dihasilkan dari sumber specific, sumber tidak specific dan bahan kimia yang dibuang. Limbah B3 memiliki sesuatu atau lebih karakteristik berikut : korosif, reraktif, mudah terbakar, mudah meledak beracun dan menyebabkan infeksi. Setiap orang atau badan usaha dilang memasukkan limbah B3 dari luar negri kedalam negri atau sebaliknyatanpa persetujuan pemerintah Republik Indonesia.